Targeting poverty to improve maternal health in Sokoto State, Nigeria - Muazu Alhaji Shamaki; Katiman Rostam; Yusuf M. Adamu (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
The health of women during pregnancy, childbirth and postpartum period is a critical measure of maternal health while maternal mortality is an important indicator of the well-being of women as well as the performance of any state’s health system. Disparities in the provision of health facilities and the relationships between poverty and maternal health are two primary community issues in the Sokoto State of Nigeria. Using relevant data from secondary sources, this study reviews maternal deaths and assesses the availability and quality of health facilities in Sokoto State. It reveals that the percentage of births attended to by a skilled professional ranged from a high of 81.8% in the SE to a low of 9.8% in Sokoto, NW. Similarly, 90.1% of women in Sokoto, NW are more likely to give birth at home compared to 22.5% in the SW. This implies that with 81.2% poverty rate and 900/100,000 maternal mortality rate in the state there is a critical relationship between poverty and the delivery of maternal health services. Thus, to improve maternal health services delivery, the study advocates for more women empowerment programmes in the state. In addition, government needs to provide more funds for the provision of more efficient maternal health facilities in order to reduce the mortality rates of women and children.